Effect of melatonin supplementation on oxidative stress parameters: A systematic review and meta-analysis. (November 2020) - Morvaridzadeh, Mojgan; Sadeghi, Ehsan; Agah, Shahram; Nachvak, Seyed Mostafa; Fazelian, Siavash; Moradi, Fatemeh; Persad, Emma; Heshmati, Javad
Graphical abstract: Highlights: Melatonin, is a tryptophan derivative antioxidant which has a key role in the regulation of daily rhythms. Melatonin indirectly improves the potential function of antioxidants enzymes, such as GPx, GR, and SOD. Melatonin significantly increases total antioxidant capacity and decreases lipid peroxidation. Abstract: Background: Oxidative stress, defined as an imbalance between pro-oxidants and neutralizing antioxidants within the body, is a growing public health concern. Oxidative stress is involved in the progression of nearly all chronic diseases. Melatonin has been suggested to reduce oxidative stress by its potential radical scavenging properties. Objective: To determine the efficacy and safety of melatonin as a therapy for the improvement of oxidative stress parameters in randomized controlled trials. Methods: A systematic database search using Scopus, PubMed/Medline, EMBASE, Web of Science, the Cochrane Controlled Register of Trials and clinicaltrials.gov (https://clinicaltrials.gov ) for studies published up to July 2020 was conducted. We included studies which investigated the effect of supplemental melatonin compared to placebo on oxidative stress parameters in unhealthy patients. Quantitative data synthesis was conducted using a random-effects model with standard mean difference (SMD) and 95 % confidence intervals (CI). Cochrane's Q and I 2 values were used to evaluate heterogeneity. Results: A total of 12 randomized controlled trials (RCTs) were eligible. The meta-analysis indicated an association between melatonin intake and a significant increase in total antioxidant capacity (TAC) (SMD: 0.76; 95 % CI: 0.30, 1.21; I 2 = 80.1 %), glutathione (GSH) levels (SMD: 0.57; 95 % CI: 0.32, 0.83; I 2 = 15.1 %), superoxide dismutase (SOD) (SMD: 1.38; 95 % CI: 0.13, 2.62; I 2 = 86.9 %), glutathione peroxidase (GPx) (SMD: 1.36; 95 % CI: 0.46, 2.30; I 2 = 89.3 %), glutathione reductase (GR) (SMD: 1.21; 95 % CI: 0.65, 1.77; I 2 = 00.0 %) activities, and a significant reduction in malondialdehyde (MDA) levels (SMD: -0.79; 95 % CI: -1.19, -0.39; I 2 = 73.1 %). Melatonin intake was not shown to significantly affect nitric oxide (NO) levels (SMD: -0.24; 95 % CI: -0.61, 0.14; I 2 = 00.0 %) or catalase (CAT) activity (SMD: -1.38; 95 % CI: -1.42, 4.18; I 2 = 96.6 %). Conclusion: Melatonin intake was shown to have a significant impact on improving Oxidative stress parameters. However, future research through large, well-designed randomized controlled trials are required to determine the effect of melatonin on oxidative stress parameters in different age groups and different disease types.